THE ROLE OF AGRICULTURAL TV PROGRAMME IN DIFFUSING MODERN AGRI. IDEAS & PRACTICES AMONG FARMERS OF BAGERAT COLLECTIV TOWN DOHUK PROVINCE IRAQ - Najim Elddin A . Saleem (Mesopotamia Journal of Agriculture)
This study is an investigation for the role of agri. TV programme in the diffusing modern agri. ideas and practices among farmers of Bagerat collective town in Dohuk province throughout the recognition of their watching the agri. TV programme and their opinions and points of views have been investigated and taken into consideration , also finding out the relationship between some respondents characteristics and their watching the programme.Data were collected by personal interviews with the help of a questionnaire.A sample of(76)farmers out of(200)was taken by using the simple random sample technique.Data were analyzed by using correlation coefficient and chi-square by using the computer. This research achieves the following results,62% of respondents watching the programme sometime , 28% Rarely, 68% did not know the day presentation of the programme , 71% understand the programmes, subjects partially, 57% of the viewers mentioned that they got little benefit of programs, subjects . The following factors showed non significant correlation with farmers, viewing the programme '' farmers, age , family size and farm size'' while '' farmers, education , type of land tenure'' showed positive relation ship with farmers, viewing the agri. TV programme. According to the findings , the researcher recommend , necessary work has to be made to change time of programme presentation , variation of presentation methods, strengthen the relation ship with the farmers, and taking care of characterstics of family members.